The ERF transcription factor LTF1 activates DIR1 to control stereoselective synthesis of antiviral lignans and stress defense in Isatis indigotica roots - Ruibing Chen; Jian Yu; Luyao Yu; Liang Xiao; Ying Xiao; Junfeng Chen; Shouhong Gao; Xianghui Chen; Qing Li; Henan Zhang; Wansheng Chen; Lei Zhang (Acta Pharmaceutica Sinica B, 2024)
Lignans are a powerful weapon for plants to resist stresses and have diverse bioactive functions to protect human health. Elucidating the mechanisms of stereoselective biosynthesis and response to stresses of lignans is important for the guidance of plant improvement. Here, we identified the complete pathway to stereoselectively synthesize antiviral (−)-lariciresinol glucosides in Isatis indigotica roots, which consists of three-step sequential stereoselective enzymes DIR1/2, PLR, and UGT71B2. DIR1 was further identified as the key gene in respoJanuary 2024nse to stresses and was able to trigger stress defenses by mediating the elevation in lignan content. Mechanistically, the phytohormone-responsive ERF transcription factor LTF1 colocalized with DIR1 in the cell periphery of the vascular regions in mature roots and helped resist biotic and abiotic stresses by directly regulating the expression of DIR1. These systematic results suggest that DIR1 as the first common step of the lignan pathway cooperates with PLR and UGT71B2 to stereoselectively synthesize (−)-lariciresinol derived antiviral lignans in I. indigotica roots and is also a part of the LTF1-mediated regulatory network to resist stresses. In conclusion, the LTF1-DIR1 module is an ideal engineering target to improve plant Defenses while increasing the content of valuable lignans in plants.